THE INFLUENCE OF WORK-LIFE BALANCE AND JOB STRESS ON TURNOVER INTENTION AMONG GENERATION Z WORKERS IN MALANG CITY - Iqbal, Moh Iqbal Haq; Almanshur, Fauzan (Universitas Bina Taruna Gorontalo, 2025)
This study aims to determine the effect of worklife balance and job stress on turnover intention among generation Z workers in Malang City. This research uses quantitative methods in order to evaluate the relevance of each variable. The population chosen in this study is generation Z workers who have entered working age, namely ages 15-27 years. In determining the sample size, the researcher used the slovin formula, the results of the slovin formula calculation obtained a sample of 100 respondents. Data collection in this study was carried out using a questionnaire. analysis tools using SmartPLS (Partial Least Square) The results of the analysis of this study indicate that worklife balance and job stress simultaneously have a significant effect on turnover intention in generation Z workers in Malang City. Partially worklife balance has a negative and significant effect on turnover intention. While work stress has a positive and significant effect on turnover intention.